RESERVOIR CHARACTERIZATION AND GAS IN PLACE ESTIMATION AT BASAL SANDSTONE RESERVOIR INTERVAL, AGASE FIELD, NORTH SUMATRA BASIN - Faturrahmi
Agase Field is an offshore gas field located in the North Sumatra Basin. The study takes focus on Late Eocene-Oligocene Basal Sandstone interval as main reservoir. This study aims to learn the geological setting, determine the depositional environment, calculate petrophysical properties, and estimate gas volume in place within the study interval. The data used in this study include wireline log data from 3 wells, rock description, well final report, drill stem test, and 16 of 2D seismic sections. Several methods used in this study are facies and depositional environment analysis, petrophysical analysis, seismic interpretation, and estimation of gas volume in place. Based on facies analysis, study interval consists of five lithofacies that are Smvf, Svf, Fsm, Fl, and Fm which after matched with their corresponding electrofacies, are grouped into four facies associations that are fluvial/distributary channel, accretionary bank, delta front, and prodelta. The association of those facies formed deltaic transition environment with fossil content refers to littoral zone. Petrophysical analysis showed that the study interval has average value of shale volume 0.22-0.54, effective porosity 0.035-0.105, and water saturation 0.58-0.82. The main geological structure based on seismic interpretation is an anticline cutted by NNW-SSE strike-slip fault who acted as a trap in Agase Field. The result of estimated gas reserved in place is 429.4 BSCF.